Content validity and internal consistency of an algorithm for cleansing wounds with granulation and necrotic tissues: Content validity and internal consistency of an algorithm for cleansing wounds with granulation and necrotic tissues - Salome, Geraldo Magela (Saúde (Santa Maria), 2024)
Protocols in the form of algorithms allow the nurse team to make rapid decisions, lowering risks and improving outcome. There is a lack of readily available protocols for the use of correct techniques and products for wound cleansing. Objective. To assess the content validity and internal consistency of an algorithm for cleansing wounds with granulation and necrotic tissues. Methods. A literature search was conducted to identify relevant studies for the construction of the algorithm, using the following descriptors: “wounds and injuries”, “algorithms”, “cleansing agents”, “therapeutic irrigation”, and “debridement” in both English, Brazilian Portuguese and Spanish. The development of the algorithm involved the planning and production of content and definition of topics. The algorithm was assessed for content validity by 20 judges and for internal consistency by 31 judges. Results. An algorithm was developed to help health professionals in the cleansing of wounds. It describes wound cleansing techniques and provides recommendations for therapeutic interventions and primary dressings, based on the type of wound tissue. The judges assessing the content validity of the algorithm reached consensus in two rounds of consultation. The algorithm showed good internal consistency with a Cronbach’s alpha of 0.851.Conclusions. The validated algorithms will provide health professionals with relevant information to choose appropriate wound cleansing techniques and therapeutic procedures according to the type of wound tissue.